2012
DOI: 10.1088/0004-637x/759/1/57
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Stars in the Light of the Massive Pulsar PSR J1614–2230

Abstract: We perform a systematic study of hybrid star configurations using several parametrizations of a relativistic mean-field hadronic EoS and the NJL model for three-flavor quark matter. For the hadronic phase we use the stiff GM1 and TM1 parametrizations, as well as the very stiff NL3 model. In the NJL Lagrangian we include scalar, vector and 't Hooft interactions. The vector coupling constant g v is treated as a free parameter. We also consider that there is a split between the deconfinement and the chiral phase … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
85
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(89 citation statements)
references
References 39 publications
(74 reference statements)
3
85
0
1
Order By: Relevance
“…(5.5) suggests that another possibility is that higher order contributions may produce a contribution with a positive sign so that eventually c 2 will converge to the SB limit. Within this scenario it appears that the (rather quick) convergence of the LN result for c 2 towards the SB could be accidental 3 . As already emphasized, at order-δ 2 the OPT considers three different topologies, including vertex corrections, which would belong to the NLO and NNLO in a 1/N c expansion.…”
Section: Numerical Resultsmentioning
confidence: 90%
“…(5.5) suggests that another possibility is that higher order contributions may produce a contribution with a positive sign so that eventually c 2 will converge to the SB limit. Within this scenario it appears that the (rather quick) convergence of the LN result for c 2 towards the SB could be accidental 3 . As already emphasized, at order-δ 2 the OPT considers three different topologies, including vertex corrections, which would belong to the NLO and NNLO in a 1/N c expansion.…”
Section: Numerical Resultsmentioning
confidence: 90%
“…This maximum mass limit is for this hadronic and quark matter EOSs. Stiffer EOS sets (like hadronic NL3 and quark quark NJL model) for the mixed hybrid star can produce much higher maximum mass [37]. From the figure it is also clear that the maximum mass of the star corresponds to a radius of about 10km.…”
Section: Resultsmentioning
confidence: 90%
“…For the mass to reach the maximum mass limit they showed that the crossover has to take place at low density and the quark matter has to be strongly interact-ing. Using very stiff EOS sets (hadronic NL3 and quark quark NJL model) the maximum mass limit for the hybrid star can be raised much higher as shown by Lenzi & Lugones [37].…”
Section: Resultsmentioning
confidence: 95%
“…In this sense, the transition occurring at µ tr should be interpreted as a "deconfinement" phase transition, which is not built from fundamental gluon dynamics, but only as an effective construction relying on the two phenomenological models involved. While a proper inclusion of confinement properties and the interplay between chiral and deconfinement phase transitions is clearly beyond the scope of this paper, in the spirit of previous works [11,49] we attempt to incorporate these effects in a crude way through the introduction of a constant shift to the NJL vacuum pressure δΩ 0 , which will be treated as a free parameter.…”
Section: A Pressure Splitting and Maxwell Constructionmentioning
confidence: 99%